Extended-Spectrum Beta-Lactamase–production in Escherichia coli isolated from door handles in Nasarawa State University, Keffi, Nigeria. Issue 8 (August 2019) - Tsaku, P.A.; Ngwai, Y.B.; Pennap, G.R.I.; Ishaleku, D.; Ibrahim, T.; Nkene, I.H.; Abimiku, R.H.
Abstract: Serious clinical concern has been raised globally over the continual evolution of pathogenic microorganisms that are resistant to several chemotherapeutic agents, especially the beta-lactam antibiotics. This study investigated ESBL-production in Escherichia coli isolated from door handles in Nasarawa State University, Keffi-Nigeria. A total of 200 door handles were sampled and 34 (17.0%) E. coli isolates were identified. The bacterial resistance profile to tested antibiotics was: tetracycline 31 (91.18%), cotrimoxazole, ceftazidime, and augmentin with 28 (82.35%). Streptomycin and ampicillin had 26 (76.47%), while ciprofloxacin, chloramphenicol, ceftriaxone, and gentamicin had 16 (47.06%), 14 (41.18%), 12 (35.29%) and 7 (20.59%) resistance profile respectively. Multiple antibiotics resistance index (MARI) ≥ 0.3 was recorded in 33 (97.06%) of the isolates. A total of 23 resistant phenotypes were observed in this study. The most common resistant phenotype was AMP-AUG-CAZ-CRO-S-CIP-SXT-TE-C with 4 appearances. Fourteen (14) of the isolates were Multidrug resistant (MDR), while 9 were extensively resistant (XDR) isolates. Fifteen (15) ESBL-producers were identified out of which bla TEM was identified in 7 of the isolates, while 10 were carriers of bla SHV, and bla CTX-M gene was not detected in any of the test isolates. This study recommends prompt action by all stakeholders in public health to prevent a potential disease burden from a superbug.